Efficacy of a bacterial insecticide, on unparasitized and parasitized lesser cotton leafworm Spodoptera Exigua Hbn. larvae by the endoparasitoid Microplitis Rufiventris kok - Kares, E. A.; El-Khawas, M. A. M.; Ebaid, G. H. (2012)
Laboratory studies were conducted to evaluate the toxic effect of the bioinsecticide Biotecht against the beginning of the third instar larvae of the lesser cotton leafworm Spodoptera exigua Hbn. (either unparasitized or parasitized ones by the endoparnsitoid Microplitis rufiventris Kok.). The LC50 values obtained for both larvae were; 13.703x104 and 17.414x10p4 (BI.U., respectively (computed from 72 hours mortality data).The mortality percentages were higher in case of unparasitized larvae comparing with the parasitized ones (where, the parasitized larvae were less susceptible to the bioinsecticide treatment than the unparasitized ones).This result was also emphasized by the total daily amounts of food consumed by both pest larvae. Therefore, using the bioinsecticide Biotecht may be recommended and could be combined with releasing the parasitoid M. rujiventris. They could be used side by side with other available safe control methods, when planning for Integrated Pest Management (1PM) strategies against the lesser cotton leafworm S. exigua.s
Includes references.
Summary in Arabic.
1
Keywords: Bacterial insecticides; Cotton leafworm -- Control; Microplitis rufiventris; Spodoptera exigua